Random walks in random environment with Markov dependence on time - Boldrighini, C.; Minlos, R.A.; Pellegrinotti, A. (Condensed Matter Physics, 2008)
We consider a simple model of discrete-time random walk on Zν, ν = 1, 2, . . . in a random environment independent in space and with Markov evolution in time. We focus on the application of methods based on the properties of the transfer matrix and on spectral analysis. In section 2 we give a new simple proof of the existence of invariant subspaces, with an explicit condition on the parameters. The remaining part is devoted to a review of the results obtained so far for the quenched random walk and the environment from the point of view of the random walk, with a brief discussion of the methods.